Improving Software Reliability Prediction Using Various Soft Computing Techniques: A Comparative Analysis of Software Reliability Prediction Using Soft Computing Techniques (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The reliability of software models is measured using the estimation of program errors. Trustworthiness is a real-world phenomenon with many related problems in real-time. A large number of soft computing techniques have been developed to find solutions to problems quickly, accurately, and acceptably but it is very hard to find the one most suitable and that is the one that can be used worldwide. In this paper, we have presented a summary of the software technologies that are possible, and then we have objectively examined the information reliability work performed by the different researchers. Furthermore, we have compared software reliability modeling techniques in software models.